COPING STRATEGY FOR ACADEMIC VALUES IN STUDENTS OF ISLAMIC COUNSELING GUIDANCE STUDY PROGRAM, FACULTY OF DA'WAH AND COMMUNICATION, UIN NORTH SUMATRA - Nurhasanah, Ummi; Mutiawati, Mutiawati (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to identify the causes and symptoms of stress, as well as the coping strategies employed by students of the Islamic Guidance and Counseling Program at the Faculty of Da'wah and Communication, State Islamic University of North Sumatra (UINSU), in facing academic pressure that affects their academic performance. A qualitative approach with a case study method was used. Data were collected through in-depth interviews, observation, and documentation involving six active students who were experiencing academic stress during their coursework. The findings indicate that academic stress is caused by multiple factors, including heavy workload, difficulty understanding course materials, limited learning resources, and pressure to maintain or improve their Grade Point Average (GPA). Symptoms of stress included physical fatigue, anxiety, difficulty concentrating, and decreased motivation. To cope with these challenges, students employed a combination of strategies: problem-focused coping such as time management and seeking additional resources; emotion-focused coping such as calming themselves and seeking emotional support; and religious coping through spiritual activities such as reciting the Qur’an, performing sunnah prayers, and sending blessings upon the Prophet. These flexible and adaptive coping strategies were found to be effective in managing academic pressure and supporting optimal academic performance.